The effect of the diaspora-combining strategy in developing the skill performance of students of the Department of Art Education in the Fundamentals of Design course (Journal of the College of Basic Education, 2022)
The current study aimed to identify the impact of the diaspora synthesis strategy in developing the skill performance of the students of the Art Education Department in the basics of design. The third included the research procedures in which the researcher followed the experimental approach to two groups (T-Z), the research community consisted of students from the Department of Art Education - College of Basic Education - Al-Mustansiriya University / the third stage, numbering 160 students, and the sample of the research was from the students of the third stage / The morning study, which numbered 90 students, and to achieve the goal of the research, the researcher identified the basics of design through (planning - composition - coloring - finding perspective - interrelationships between elements and foundations), and the researcher used two measurement tools (cognitive achievement test - skill test) to measure students' achievement The two research groups (T-Z) and this test was characterized by honesty and reliability, and the statistical bag (Spss) was used as it is the most appropriate for his current study, as it was shown that the students of the experimental group who studied According to the scattering strategy on the students of the control group who studied in the traditional way.